Multicultural Class Program as a Means of Strengthening Pancasila Character at Bakti Karya Vocational High School - Galuh Ibrahim; Encep Syarief Nurdin; Mupid Mupid; Yadi Ruyadi (Jurnal Moral Kemasyarakatan, 2025)
Multicultural education and the cultivation of Pancasila values are important elements in building an inclusive and tolerant national character in Indonesia. This study analyzes the implementation of Pancasila values in the multicultural class program at the Bakti Karya Parigi Vocational High School (SMK). This article aims to explore the cultivation of Pancasila values at SMK Bakti Karya Parigi through a multicultural class program. This study uses a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation. The study's results show that the multicultural classroom program has successfully incorporated Pancasila values into students' daily lives. This has led to positive changes in how they behave toward cultural diversity, such as becoming more independent, working together, and tolerant. The study concludes that multicultural classroom programs have proven to be effective in introducing and practicing Pancasila values in students' lives, both in the school environment and in their social interactions. It's clear from this study that there needs to be a curriculum document to make sure that the multicultural classroom program works with the national goals of building character through Pancasila values in secondary schools.